An Investigation of the Managerial Competencies of Cultural Managers from the Perspective of Future Culture Scenarios - Shadkam , Fatemeh; Rashidpoor, Ali (Future of Work and Digital Management Journal, 2025)
The aim of the present study was to examine the managerial competencies of cultural managers. This study was conducted using a qualitative methodology, employing field methods, semi-structured interviews, coding, questionnaires, and document analysis. The statistical population of the research included all experts in the field of futures studies related to the competencies of cultural managers. The research sample consisted of 13 experts selected through snowball sampling. Questionnaires related to the study variables were designed and distributed among the participants. After data collection, the information was analyzed through content analysis and the Delphi method by consulting experts, using MAXQDA2018 software. The results of the qualitative analysis indicated that futures studies in this domain require consideration of 152 subcategories. In the selective coding phase, the dimensions of the coding paradigm were identified, including six core categories: causal conditions, barriers, intervening conditions, contextual conditions, strategies, and consequences. One of the most important domains and causal conditions in the futures studies of cultural managers’ competencies was the role of managerial skills. This is because cultural organizations, due to their unique characteristics, require managers who possess not only specialized knowledge in the field of culture but also managerial skills.